DEVELOPMENT OF PRACTICAL AND DEPLOYABLE TEXT-BASED ANTI-GPS SPOOFING MECHANISMS - 528, Dr. Sunny Arora, Dr.Vijay Bhardwaj (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The GPS system's anti-spoofing (AS) mechanism is intended to protect against potential spoofers (or jammer). A spoofer puts out a sign that has all the earmarks of being GPS and endeavors to trick the beneficiary into following the erroneous sign. The Global Navigation Satellite System is altogether utilized in current military and common route and situating frameworks (GNSS). The strength of the satellite sign at the ground, on the other hand, is relatively low, making it susceptible to interference. The development of interference suppression technology for satellite navigation systems has a wide range of practical applications. Jamming and spoofing are two types of GNSS interference. We used Text extraction from panoramic photos is one of the most essential aspects of our investigation. Some of the techniques we use include image deblurring, text detection, and text recognition. They are critical to our system's capacity to extract more accurate textual data from panoramic images photographs. The text detection process would begin with the input image. Multiple text boxes appear in the image as a result. The viability the effectiveness of a realtime text-based anti–GPS spoofing system is examined. According to analysis and driving simulation testing in two cities, our method may achieve promising results with the GSV reference dataset for broad GPS spoofing attack tactics. The idea is to take advantage of the cheaper cost to improve the system's effectiveness and robustness in detecting broad spoofing attacks